An integrated equalization charger for series‐connected energy storage cells. (22nd March 2022) - Yang, Xiaoguang; Jia, Zhe; Wang, Dexin; Nie, Baoxin; Zhao, Xiaobing; Su, Yukui
Summary: This paper proposes an integrated equalization charger that integrates the charger, module‐level equalizer, and cell‐level equalizer into the energy storage system, which greatly simplifies the system. The proposed control strategy can not only improve the equalization charging characteristics of the system, such as fast balancing speed and high efficiency, but also enable all active switches to achieve zero voltage switching (ZVS) operation. The established analytical models and control block diagram facilitate the design and development of the converter. The proposed converter can balance the cells while charging the string. An experimental prototype was developed, and the experimental results verified the theoretical analysis and demonstrated the characteristics of the proposed converter. Abstract : This paper proposes an integrated equalization charger that integrates the charger, module‐level equalizer, and cell‐level equalizer into the energy storage system, which greatly simplifies the system. The proposed control strategy can not only improve the equalization charging characteristics of the system but also enable all active switches to achieve zero voltage switching (ZVS) operation.